The Effectiveness of Sacral Neuromodulation on a Patient with a Previous Successful Cystoplasty Augmententation: A Case Report - Sharifiaghdas, Farzaneh (Urology Journal, 2020)
This report is about the effectiveness of sacral neuromodulation in a 32-year-old woman with a history of augmented cystoplasty who required clean intermittent catheterization. She had referred to our center with a medical history of bilateral vesicoureteral reflux because of neuropathic lower urinary tract dysfunction. We successfully did a sacral neuromodulation on her which lead to a promising result.